Challenges to US hegemony : The case of Lula's Brazil - Vasileiou, Florentia; Eberle, Jakub; Weinfurter, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
After his victory, Lula has been forthright about his vision of a Brazil that actively engages in foreign policy endeavours to restore its global position as a voice of the Global South independent of outside influence, particularly the US. This dissertation aims to determine whether Lula's Brazil could challenge US hegemony, specifically focusing on three separate domains: political, trade and dollar hegemony. Brazil has the ambition and ability to challenge the United States' dollar and trade hegemony through the promotion of both BRICS and regional currencies, as well as changes in trade operations aimed at opposing the dollar. Nonetheless, it is unclear whether Brazil can truly challenge US political hegemony in the near future, despite evidence that Brazil intends to strengthen its political dominance through BRICS and regional institutions.
Vedoucí práce: Jakub Eberle
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses